ปัจจัยที่ส่งผลต่อผลผลิตข้าวของเกษตรกรชานเมือง: กรณีศึกษาบริเวณคลองหกวา (FACTOR AFFECTING RICE YIELD OF SUBURB FARMER: CASE STUDY OF KLONG HOK WAH REGION) - ประยุกต์วงศ์, วรรณา (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2018)
The objectives of this research were to study the general information of suburb farmer in Klong Hok Wah Region, to describe a production pattern of suburb farmer in Klong Hok Wah Region and to analyze factors affecting rice yield of suburb farmer. The population of this research was suburb farmer were registered by Agricultural Ministry in in Klong Hok Wah Region. The purposive sampling was applied in each village to cover whole region. 40 suburb farmers were selected as the sample size by purposive sampling methodology. Statistical methodologies were arithmetic mean, standard deviation as well as the average of rice product per rai in each category of suburb farmer. The research found that the majority of suburb farmers were men which were 50 years old average with the educational level of Pathomsuksa. The majority of production land was rented by suburb farmer which average land holding was 34 rai. The major capital of rice production was suburb farmer’s owner. The study of rice production pattern were to grow rice by buying a rice seed of RD 47 and RD 31, using chemical fertilizer and pesticide and having sub-contractors in every step of production process. The outputs of off-season rice production in the 2014 year were 741 kilogram per rai and were sold to a middleman at a price about 6,000-7,000 Baht per ton. The study of factor affecting rice product per rai of suburb farmers was land holding type and number of family member to help in farm. Although suburb farmers were a manager who hired sub-contractors to work on farm completely, there still was necessary for an extra family member, except himself to take care with their farm which made a rice product increased.